Rapid urbanization leads to decline in forest cover and ecosystem services in India: insights from 10-m ESA Sentinel-2 land use land cover product - Sumanta Chatterjee; Smruthi Sagarika Mahapatra; Amaresh Kumar Nayak; Vikas Kumar Rai; Prakash Jha; Seyed Roohollah Mousavi (Theoretical and Applied Climatology, 2025)
This research investigates short-term land use and land cover (LULC) changes and their impact on ecosystem services in eastern India from 2017 to 2022. It highlights how LULC alterations affect hydrodynamic variables and social factors. Using a globally established database, Ecosystem Service Values (ESV) were assessed through LULC analysis. The findings reveal a concerning decline in rainfall and vegetation health over the study period, suggesting potential climate change impacts. Notably, rainfall deviations in 2017 and 2022 were greater than the 30-year long-term average. Analysis using 10-m ESA Sentinel-2 remote sensing data indicated a 39.14% urban area expansion, while forest cover decreased by 9.76%, leading to an estimated loss of US$1,216 million in ESV. Conversely, ESV from croplands increased slightly by US$0.35 million, indicating possible improvements in irrigation infrastructure in Odisha. Wetland ESV also rose by 2.14% (US$8.81 million). The study highlights the critical role of LULC changes in influencing hydrodynamic variables such as rainfall and soil moisture, as well as social factors like urbanization. Understanding these interconnections is essential for effective land use planning and management. The findings can inform future policies, particularly in ecosystem service payments and rural livelihood improvements, ensuring sustainable development in the region. Graphical Abstract